Sistema de riego automatizado por aspersión utilizando un aerogenerador (2013)
The purpose of this degree project is to implement in the municipality of San Cristóbal Bolívar, a novel irrigation system that is friendly to the environment, which allows safety for the life and physical integrity of both animals (fauna) and animals to prevail. human beings, with the highest percentage of effectiveness possible.